RETRACTED: Interoperable square‐circular coupled coils for wireless electric vehicle battery charging system with different misalignments - Charan Singh Banothu; Srinivasa Rao Gorantla; Rakada Vijay Babu Attuluri; Geetha Reddy Evuri (IET Power Electronics)
Abstract A substantial interest in inductive power transfer (IPT) is due to its straight forwardness and dependability in charging electric vehicle (EV) batteries for researchers. The mutual inductance (MI) plays a critical role in the IPT system as it enables efficient power transfer. Therefore, it is imperative to examine the MI between the two coils that are connected through inductive coupling. This work investigates the MI and efficiency of connected coils in interoperable conditions. The transmitter coil is arranged in the shape of a square (TxS), whereas the reception coil is arranged in the shape of a circle (RxC). A concise and user‐friendly collection of design guidelines for S‐S compensated resonant inductive power transfer (SS‐RIPT) systems the design concepts efficiently mitigate the possibility of systematically and unambiguously setting the specifications for a given load profile. A 3.6‐kW setup has been constructed and validated by finite element analysis and experimental testing, following the design specifications. The availability of suitable testing equipment in the laboratory influenced the choice of a resonance frequency and output voltage for a 3.6 kW system.